CFOs' audit experience and corporate disclosure quality: evidence from China. (2nd February 2022) - Li, Piao; Song, Chang; Wang, Jenny Jing; Zheng, Hongrui
Abstract: This paper examines the effect of the prior audit experience of chief financial officers (CFOs) on corporate information disclosure. Utilising a sample of 25, 480 firm‐annual observations of A‐share Chinese listed companies over the period 2007–2019, we find that CFOs with audit experience improve the quality of corporate information disclosure. We also find that Big 4 auditor CFOs have a more positive influence on corporate information. Finally, we find that the power of CEOs influences the effect of CFOs' audit experience on corporate disclosure quality. This study contributes to the selection of CFOs by listed companies with the aim to improve corporate governance mechanisms.